Review on Metal Telluride Thin Films - Ho, S.M. (2015)
The main objective of this review paper is to study the preparation of metal telluride thin films using various deposition techniques. A series of experiments were carried out in order to obtain metal telluride thin films by using different precursors. Literature survey indicated that the obtained films were considered as the best candidate for use in electric and optoelectronic devices.